Editorial - Oniwide, Oyetola (NIU Journal of Legal Studies, 2026)
This issue of NIU Journal of Legal Studies touches on the Issues such as Justice for Victims of Medical Malpractice, Tax Laws, Environmental and Socioeconomic Rights and so on. One of the papers, in this edition, reveals that the present financial architecture for medical malpractice litigation in Nigeria is inadequate and constitutes significant barrier to access to justice and recommends a combination of legislative and policy reforms such as compulsory malpractice insurance, establishment of statutory compensation fund and regulated third-party funding. Another paper argues that Nigeria is transitioning from a permissive tax planning regime to a rules-based and substance-oriented system, inspired by Base Erosion and Profit Shifting (BEPS) principles, through doctrinal and comparative analysis with these countries and the OECD frameworks. The paper therefore, concludes that it is inevitable for corporate taxpayers to avoid aggressive tax planning and embrace sustainable tax compliance. In sum, this issue of NIU Journal of Legal Studies features many empirical and theoretical based articles which can be of great benefit to every reader.